2016
DOI: 10.1016/j.neubiorev.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Functional reorganisation in chronic pain and neural correlates of pain sensitisation: A coordinate based meta-analysis of 266 cutaneous pain fMRI studies

Abstract: HighlightsNeural maladaptation in chronic pain conditions is poorly understood.Large scale coordinate based meta-analysis of 266 cutaneous pain fMRI was performed.Results support a shared neural pain response in chronic pain and healthy subjects.Hyperalgesia leads to increased activation in an unchanged neural pattern.Chronic pain patients show functional reorganisation depending on stimulation site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(97 citation statements)
references
References 95 publications
5
90
2
Order By: Relevance
“…In systematic reviews, we considered all articles that the authors identified for inclusion. If a systematic review included a meta-analysis of experimentally induced pain in healthy volunteers (e.g., Friebel et al, 2011;Duerden et al, 2013;Jensen et al, 2016;Tanasescu et al, 2016), we automatically included all studies within the meta-analysis to be screened for full text.…”
Section: Reference Search From Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…In systematic reviews, we considered all articles that the authors identified for inclusion. If a systematic review included a meta-analysis of experimentally induced pain in healthy volunteers (e.g., Friebel et al, 2011;Duerden et al, 2013;Jensen et al, 2016;Tanasescu et al, 2016), we automatically included all studies within the meta-analysis to be screened for full text.…”
Section: Reference Search From Reviewsmentioning
confidence: 99%
“…Prior meta-analyses have identified several brain regions that are engaged under pain conditions, including the secondary somatosensory cortex (SII), insula, cingulate cortex, and thalamus. Other regions have been identified somewhat less reliably, including primary somatosensory cortex (SI), striatum, cerebellum, supplementary motor area (SMA), primary motor area (M1), periaqueductal gray (PAG), prefrontal cortex (PFC), certain areas in parietal cortices, and the parahippocampal gyrus (Apkarian et al, 2005;Duerden & Albanese, 2013;Farrell et al, 2005;Jensen et al, 2016;Lanz et al, 2011;Peyron et al, Running title: Pain fMRI Meta-analysis 2000; Tanasescu et al, 2016). Subsequent meta-analyses have sought to parse this pain network further by investigating neural responses specific to different pain induction modalities, such as thermal pain (Farrell et al, 2005;Friebel et al, 2011;Jensen et al, 2016), and to different stimulation location (Duerden & Albanese, 2013;Jensen et al, 2016;Lanz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Full meta-analyses are a study in themselves and beyond this demonstration, so data adapted from two previously published analyses [29,30] are used. The first is a meta-analysis of VBM studies of clinically isolated syndrome (CIS) and multiple sclerosis (MS); subjects diagnosed with CIS are at risk of developing clinically definite MS, which is known to result in grey and white matter atrophy.…”
Section: Coordinate Based Random Effect Analysis Of Real Datamentioning
confidence: 99%
“…A recent meta-analysis including a sub-analysis of mood effects on hyperalgesia was unfortunately limited by few citations reporting mood in their subjects [13]. Additional experiments are therefore needed 1) that directly test for mood alterations (e.g.…”
mentioning
confidence: 99%